2021
DOI: 10.1021/acs.molpharmaceut.1c00297
|View full text |Cite
|
Sign up to set email alerts
|

Non-Viral Vector-Mediated Gene Therapy for ALS: Challenges and Future Perspectives

Abstract: Amyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease, for which no effective treatment is yet available to either slow or terminate it. Recent advances in gene therapy renew hope for developing an effective approach to control this disease. Non-viral vectors, such as lipid-and polymer-based nanoparticles, cationic polymers, and exosomes, can effectively transfer genes into primary neurons. The resulting gene expression can be long-term, stable, and without immunological complications,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 143 publications
0
23
0
Order By: Relevance
“…The effects observed in mice, such as preventing weight loss and impaired neuromuscular function, as well as increased survival, support the effectiveness of this technology [ 101 ]. The therapeutic approach using RNAi has the potential to be another form of gene therapy for ALS but still needs to overcome such difficulties as in vivo instability, lack of siRNA specificity and potential toxicity of RNAi-based technologies [ 102 ].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…The effects observed in mice, such as preventing weight loss and impaired neuromuscular function, as well as increased survival, support the effectiveness of this technology [ 101 ]. The therapeutic approach using RNAi has the potential to be another form of gene therapy for ALS but still needs to overcome such difficulties as in vivo instability, lack of siRNA specificity and potential toxicity of RNAi-based technologies [ 102 ].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…In this research, the brain region targeted for BBB opening was the eloquent primary motor cortex, and the process was found to be safe, feasible, and reversible. For patients with ALS, BBB opening is used to introduce agents such as nonviral vectors that transport therapeutic genetic elements into neurons; it is therefore essential that these agents are not damaged as they travel through the BBB ( 104 ).…”
Section: Fus-mediated Bbb Openingmentioning
confidence: 99%
“…Some scholars suggested that EVs can act as a non-viral vector for the delivery of genetic material to treat ALS due to their ability to transport various cellular entities across the BBB. Surprisingly, the research on using EVs for gene delivery in the treatment of ALS is very few ( Ediriweera et al, 2021 ). Nevertheless, this aspect of research work has become an interesting subject with the thriving advances in nanotechnology.…”
Section: Extracellular Vesicles As Drug Delivery Vehicle For Amyotrophic Lateral Sclerosismentioning
confidence: 99%